AgriTech4Kenya Innovation Challenge 2024: Bootcamp report - Menza, Gianpiero; Khader, Taija; Wafullah, Nekesah (2024)
The AgriTech4Kenya Innovation Challenge Bootcamp, held from November 25 to 29 2024 at the Brackenhurst Conference and Retreat Centre in Limuru, brought together 25 innovative early-stage projects representing diverse regions and priorities within the Agri-Tech sector. Over the course of four days, these innovators engaged with partners, explored Kenya’s Agri-Tech ecosystem, and refined their solutions through workshops, expert masterclasses, farm visit, and one-on-one mentoring sessions.